KEMAMPUAN MENULIS JURNAL LITERASI SASTRA SISWA SMA NEGERI 7 BANJARMASIN - Syaifullah Syaifullah (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2018)
AbstractWriting Ability on Literacy Literature Journal by Students of SMA Negeri 7 Banjarmasin. Journal ofliteracy literature is one of the students work in the form of book reports after the basic literacy habituationis done. This study examines (1) the content of literacy literature journal, and (2) the constraints inwriting the literacy literature journal content of SMA Negeri 7 Banjarmasin students. This research usedescriptive qualitative approach. Data and sources of data in this research is the result of writing in theliteracy literature journal by students of SMA Negeri 7 Banjarmasin. Data collection techniques in thisstudy by doing observation, questionnaire, interview, population and sample. The population in thisstudy is the eleven grade students. The technique used is random sampling, which is by taking 10% oftotal population 311 counted 32 samples. Data analysis technique techniques of this research are throughthree steps such as reduction data, presentation data and conclusion by using the formula of the averagelevel mastery. The results obtained from literacy literature journal writing skills were viewed based onfive rating categories with scores; (1) content 79.6%, (2) organization 75.3%, (3) vocabulary 67.6%, (4)syntax 75.4%, and (5) mechanism 92.6%. So, the average literacy literature writing skills of SMA Negeri7 Banajarmasin students get good assessment qualification, that is 78.1% located at interval 75-84%.The constraints found in the literacy literature journal writing rests on two main factors, namely internalfactors and external factors. The constraints found in the internal factor includes; (1) determining themain idea of the story, (2) the final/ inductive topic, (3) the development of the paragraph, and (4) theuse of spelling and punctuation, while the constraints found in the external factor includes; (1) limitedtime, and (2) limited reading sources.Key words: writing ability, literacy literature journalAbstrakKemampuan Menulis Jurnal Literasi Sastra Siswa SMA Negeri 7 Banjarmasin. Jurnal literasi sastramerupakan salah satu karya siswa berbentuk laporan hasil bacaan setelah kegiatan pembiasaan literasidasar dilakukan. Penelitian ini mengkaji tentang (1) isi jurnal literasi sastra, dan (2) kendala-kendaladalam penulisan isi jurnal literasi sastra siswa SMA Negeri 7 Banjarmasin. Peneltian ini menggunakanpendekatan deskriptif kualitatif. Data dan sumber data penelitian ini ialah hasil tulisan siswa padajurnal literasi sastra. Teknik pengumpulan data dengan melakukan observasi, angket, wawancara, sertapopulasi dan sampel. Populasi dalam penelitian ini adalah siswa kelas XI. Teknik yang digunakan dalampengambilan sampel adalah random sampling, yaitu dengan mengambil 10% dari jumlah populasi 311279sebanyak 32 sampel. Teknik analisis data melalui langkah reduksi data, penyajian data dan penarikankesimpulan dengan menggunakan rumus rata-rata tingkat penguasaan. Hasil penelitian yang diperolehdari kemampuan menulis jurnal literasi sastra dilihat berdasarkan lima kategori penilaian dengan hasil;(1) isi 79,6%, (2) organisasi 75,3%, (3) kosakata 67,6%, (4) sintaksis 75,4%, dan (5) mekanisme 92,6%.Rata-rata kemampuan menulis jurnal literasi sastra siswa SMA Negeri 7 Banajarmasin mendapatkankualifikasi penilaian yang baik dengan nilai 78,1%. Kendala yang ditemukan terdapat pada dua faktorutama, yaitu faktor internal dan faktor eksternal. Pada faktor internal meliputi; (1) menentukan idepokok cerita, (2) topik akhir/induktif, (3) pengembangan paragraf, dan (4) penggunaan ejaan dan tandabaca, sedangkan pada faktor eksternal; meliputi (1) keterbatasan waktu, dan (2) sumber bacaan.Kata-kata kunci: kemampuan menulis, jurnal literasi sastra